Crop intensification with sustainable practices did not increase N2O emissions - Casanave Ponti, Sheila Mailén; Videla, Cecilia; Monterubbianesi, María Gloria; Andrade, Fernando Hector; Rizzalli, Roberto Héctor (Elsevier, 2020)
Nitrous oxide (N2O) is the most important greenhouse gas produced by agricultural soils and is a byproduct of microbial nitrification and denitrification processes. The N2O emission rates depend on soil, climatic and management factors. The objectives of this study were i) to evaluate N2O emissions during a barley crop period and its subsequent barley-maize interperiod, under two management systems, and ii) to relate the N2O flux rates with soil mineral N content, waterfilled pore space (WFPS) and soil temperature. These periods are part of threeyear crop sequence (barley - maize - soybean) of a long-term experiment under two management systems, ecological intensification (EI) and farmer current practices (FP). For the analyzed period, the EI system included a cover crop after barley and higher N rates, with split application, compared to FP. N2O emissions were monitored weekly using a static chambers method. Simultaneously, the mineral N content (NO3–N and NH4+- N), WFPS and soil temperature at 10 cm depth were determined. The flux of N2O-N ranged from 6 to 61 μg of N2O-N m2 h-1 during the barley crop and between 1.5 and 47 μg of N2O-N m2 h-1 during the barley-maize interperiod, without significant differences between management systems. N2O emissions were controlled by soil temperature and %WFPS according to a multiple regression analysis. NH4+-N and NO3–N soil content did not enter into any model as a regulator of N2O flux. During the barley period there was a significant effect of the WFPS×soil temperature interaction since N2O emissions increased with soil temperature only at WFPS > 40 %. During the barley-maize interperiod, there were significant positive effects of WFPS and temperature on N2O emissions with no significant WFPS x temperature interaction. The cumulative emissions of N2O-N were not different between management systems during the barley crop (IE=646 and FP=757 g N2O-N ha-1) or during barley-maize interperiod (IE=816 and FP=754 g N2O-N ha-1). Throughout the study period, the combination of management practices in EI increased barley yield and did not increase N2O emissions with respect to FP, despite higher N rates and the inclusion of cover crop in EI. The intensification of crops does not necessarily increase N2O emissions from agricultural soils as long as the crops are conducted with appropriate management practices.